Pengaruh Variasi Konsentrasi Metanol Terhadap Karakteristik Bahan Bakar Biogasoline Berbahan Baku Limbah Plastik Hasil Pirolisis - Sidabutar, Rotama Arifin; Siahaan, Enzo W.B; Sitanggang, Hodmiantua (Jurnal Teknik Mesin, 2024)
The increasing volume of plastic waste and the depletion of fossil fuel reserves have encouraged the search for renewable energy alternatives. This study examines the use of the pyrolysis process on plastic waste to produce biogasoline and optimises the characteristics of the fuel by adding methanol concentration. The pyrolysis process, conducted at 3500C, produces plastic oil, which is then mixed with methanol in various concentrations (5%, 10%, 20%, and 30%). The effect of methanol addition on the physical characteristics of biogasoline, including the Research Octane Number (RON) value, density, viscosity, heating value, and flash point, was analysed. The results showed that the addition of methanol concentration gave the highest RON value of 83.3, while the 10% methanol concentration produced the highest calorific value of 53,865 j/g. The addition of methanol concentration also had a positive effect on increasing the flash point of the fuel. This study also shows the potential of biogasoline made from plastic waste as an efficient and environmentally friendly alternative fuel.